2020
DOI: 10.1007/s00259-020-04874-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic in nuclear medicine departments: preliminary report of the first international survey

Abstract: Purpose Coronavirus disease-19 (COVID-19) pandemic is challenging the availability of hospital resources worldwide. The Young Group of the Italian Association of Nuclear Medicine (AIMN) developed the first international survey to evaluate the impact of COVID-19 in nuclear medicine (NM). The aim of this study was to perform a preliminary report of the ongoing survey. Methods A questionnaire of thirty questions was prepared for all NM professionals addressing three main issues: (1) new scheduling praxes for NM d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 34 publications
3
41
0
1
Order By: Relevance
“…Several surveys have evaluated the impact of COVID-19 on nuclear medicine services [3,4,5,6,7]. All the surveys showed that COVID-19 had resulted in a signi cant decline in nuclear medicine scanning across the world, with some centres experiencing a decrease in activity of up to 85% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several surveys have evaluated the impact of COVID-19 on nuclear medicine services [3,4,5,6,7]. All the surveys showed that COVID-19 had resulted in a signi cant decline in nuclear medicine scanning across the world, with some centres experiencing a decrease in activity of up to 85% [7].…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, Nuclear Medicine (NM) departments have been involved in several changes and issues, such as new scheduling praxes for NM diagnostic and therapeutic procedures, the assistance of patients with diagnosed or suspected COVID-19, and the prevention of COVID-19 spreading in the departments. For these reasons, some research groups promoted different international surveys to understand the impact of the pandemic on NM departments [ 1 – 3 ].…”
mentioning
confidence: 99%
“…The Young Group of the Italian Association of Nuclear Medicine (AIMN) developed the first international survey to evaluate the impact of COVID-19 in NM and performed a preliminary report of the obtained responses [ 1 ]. Two-hundred and ninety-six individual responders from 220 departments were evaluated.…”
mentioning
confidence: 99%
See 2 more Smart Citations